Systemic Antibiotics Versus Topical Treatments for Chronic Discharging Ears with Underlying Eardrum Perforations - Masum, SHIA; Fakir, MAY (Journal of Dhaka Medical College, 2011)
Context: Chronic suppurative otitis media (CSOM) is a common cause of preventable hearing impairment worldwide, particularly in low and middle-income countries. Untreated CSOM may result in permanent hearing loss, which in turn, may result in speech and language delays or permanent learning disabilities, as well as behavioural problem. Of the treatment options, the efficacy of using only topical antibiotics and combination of systemic antibiotics and topical antibiotics are most disputable. The present study was undertaken to investigate the role of adjuvant systemic antibiotics in the treatment CSOM. Methods: A randomized clinical trial was carried out on children with chronic suppurative otitis media at the ENT outpatient department of Dhaka Shishu Hospital from January to December 2009. Any patient presenting with a stage of ear disease in which there is chronic infection of the middle ear cleft, a non-intact tympanic membrane and a history of discharge for at least two weeks was considered as a case. A total of 112 cases of chronic suppurative otitis media were consecutively enrolled in the study. Of them, 72 completed 3rd follow up visit and hence, considered evaluable. Results: The results of the study demonstrated that the study groups were almost identical in terms of age, sex, socioeconomic class and residence. The peak age incidence of chronic suppurative otitis media was found between 4-6 years (around 75%). In both the groups, the patients were predominantly male, belonged to poor and lower middle class families and slum dwellers. No significant difference was observed between the study groups in terms of primary and secondary outcome as well as the complications encountered by the patients. Patients of who received combined therapy, 70% of them showed resolution of otorrhoea by 2 weeks and 95% by 3 weeks, which in the patients of topical antibiotics alone was 50% and 87.5% respectively. The trial did not show any adverse event except tinnitus complained by a few patients in both groups. Conclusion: Topical quinolone antibiotics (ciprofloxacin) are equally effective as topical plus oral antibiotics (ciprofloxacin) for resolution of otorrhoea from uncomplicated CSOM. However, for faster resolution of otorrhoea, a short course systemic antibiotic can be added. Key words: Chronic suppurative otitis media (CSOM); topical antibiotics; topical plus systemic antibiotics; primary outcome; secondary outcome. DOI: 10.3329/jdmc.v19i2.7075 J Dhaka Med Coll. 2010; 19(2) : 86-90